Effects of Covid-19 lockdowns on symptoms of social anxiety in a sample of university students - Eyþór Daði Hauksson 1997- (2022)
With people socializing every day by going to school, work, and other social environments, the Covid-19 pandemic has been met with extensive social distancing measures. These measures put a big part of people’s everyday life on hold with perhaps the biggest impact on their social lives. The threat of a global pandemic and imposed measures of social lockdown can reasonably be expected to exacerbate mental health problems, such as social anxiety where avoidance of social situations is a key maintenance factor of the problem. Will the Covid-19 lockdowns have effects on social anxiety symptoms on a sample of university students in Iceland? The current study used a dependant t-test to measure between the pre Covid-19 and post Covid-19 time periods. Participants consisted of 378 students in Reykjavik University from the ages 18 to 66+ years old. Gender ratio was 50,3% female, 30,6% male and 19,1% other or missing. Participants were asked to self-evaluate symptoms on various anxiety disorder scales, such as SIAS/SPS6. Results showed an increase in social anxiety symptoms and significant difference between the two time periods. These findings can shine a light on how the pandemic has impacted people‘s mental health, especially social anxiety. Keywords: Covid-19, lockdown, social anxiety, social distancing, Social phobia scale (SPS), Social interaction anxiety scale (SIAS) Á hverjum degi þar sem fólk er félagslega virkt í alls konar hvunndagsiðju, svo sem að fara í skóla, vinnu og víðar í umhverfi sem iðar af félagslífi þá hefur Covid-19 heimsfaraldurinn sett strik í reikninginn í félagslíf margra með umfangsmiklum samkomutakmörkunum og bönnum. Þessar aðgerðir settu stóran hluta af hversdagslífi fólks í pásu og þar af mest félagslíf fólks. Það er hægt að ganga út frá því að ógn frá heimsfaraldri stafi á andlega líðan fólks, þar á meðal félagskvíða þar sem einn aðal viðhaldsliður félagskvíða er forðun frá félagslegum aðstæðum. Munu Covid-19 samkomutakmanir hafa áhrif á einkenni félagskvíða á úrtaki íslenskra ...